Immunoinformatics-aided rational design of a multi-epitope vaccine targeting feline infectious peritonitis virus - Chawla, Mohit; Cuspoca, Andrés Felipe; Akthar, Nahid; Magdaleno, Jorge Samuel Leon; Rattanabunyong, Siriluk; Suwattanasophon, Chonticha; Jongkon, Nathjanan; Choowongkomon, Kiattawee; Shaikh, Abdul Rajjak; Malik, Tabarak; Cavallo, Luigi (Frontiers in Veterinary Science, 2023)
Feline infectious peritonitis (FIP) is a grave and frequently lethal ailment instigated by feline coronavirus (FCoV) in wild and domestic feline species. The spike (S) protein of FCoV assumes a critical function in viral ingress and infection, thereby presenting a promising avenue for the development of a vaccine. In this investigation, an immunoinformatics approach was employed to ascertain immunogenic epitopes within the S-protein of FIP and formulate an innovative vaccine candidate. By subjecting the amino acid sequence of the FIP S-protein to computational scrutiny, MHC-I binding T-cell epitopes were predicted, which were subsequently evaluated for their antigenicity, toxicity, and allergenicity through in silico tools.Our analyses yielded the identification of 11 potential epitopes capable of provoking a robust immune response against FIPV. Additionally, molecular docking analysis demonstrated the ability of these epitopes to bind with feline MHC class I molecules. Through the utilization of suitable linkers, these epitopes, along with adjuvants, were integrated to design a multi-epitope vaccine candidate. Furthermore, the stability of the interaction between the vaccine candidate and feline toll-like receptor 4 (TLR4) was established via molecular docking and molecular dynamics simulation analyses. This envisages good prospects for future experimental validation to ascertain the efficacy of our vaccine candidate in inducing a protective immune response against FIP.